Real-World Lenvatinib Versus Sorafenib in Patients With Advanced Hepatocellular Carcinoma: A Propensity Score Matching Analysis - Kuo, Yuan-Hung; Lu, Sheng-Nan; Chen, Yen-Yang; Kee, Kwong-Ming; Yen, Yi-Hao; Hung, Chao-Hung; Hu, Tsung-Hui; Chen, Chien-Hung; Wang, Jing-Houng (Frontiers in Oncology, 2021)
Background: Lenvatinib is approved for patients with advanced hepatocellular carcinoma (HCC) due to its non-inferiority to sorafenib of overall survival (OR) in clinical trials. This study was to compare the effectiveness and safety of lenvatinib and sorafenib in the real world. Methods: We retrospectively evaluated 338 patients with unresectable HCC who had undergone lenvatinib or sorafenib treatment between January 2018 and August 2020. Propensity-score matching analysis was performed with a 1:2 ratio to reduce the real-life baseline difference between the two groups. Results: A total of 210 patients (Male/Female: 150/60, mean age: 65.8 years) were recruited including 70 patients in the Lenvatinib group and 140 patients in the Sorafenib group. Compared with sorafenib, lenvatinib had significantly longer progression-free survival (PFS) (5.2 vs 3.3 months, p=0.019) but similar OR (13.3 vs 11.8 months, p=0.714). Additionally, lenvatinib had better disease control rates (62.3% vs 48.6%, p=0.029) and equivalent incidences of treatment-related adverse events over sorafenib. In multivariate analysis, lenvatinib was associated with better PFS over sorafenib (hazard ratio: 0.49, 95% confidence interval: 0.3-0.79, p=0.004) after adjustments of albumin-bilirubin grade and alpha-fetoprotein level; however, different agents using lenvatinib or sorafenib did not contribute to OS, whether in univariate or multivariate analysis. Patients who failed lenvatinib had a lower proportion of having sequential systemic therapies compared with the Sorafenib group (36.2% vs 47.8%, p=0.002). The most frequently used sequential therapy following lenvatinib and regorafenib was chemotherapy (n=9, 42.8%) and regorafenib (n=33, 50.8%), respectively. Conclusions: In clinical real-life practice, lenvatinib illustrated promising survival benefits and acceptable safety for patients with unresectable HCC, while reducing the risk of progression disease compared with sorafenib. Additionally, lack of approved post-lenvatinib systemic therapies is a serious issue in the real world.